Enhancing SME Export Performance through Export Sharing Communities, Export Market Orientation, and Export Digital Agility: A Mediation Analysis - Bintoro Bagus Purmono; Ramadania; Wenny Pebrianti (Ilomata International Journal of Management, 2026)
Small and Medium Enterprises (SMEs) in Indonesia continue to face a persistent export performance gap compared with comparable ASEAN economies. Although previous studies have examined collaborative networks, market orientation, and digital capabilities separately or in pairs, little is known about their integrated role in improving SME export performance. This study addresses this gap by developing and testing an empirical model integrating Export Sharing Community (ESC), Export Market Orientation (EMO), and Export Digital Agility (EDA), with EMO and EDA proposed as complementary mediators. Using a cross-sectional survey of 215 exporting SMEs across Indonesia, data were collected through structured questionnaires employing five-point Likert scales adapted from validated measures. Structural Equation Modeling (SEM–AMOS 24) was used to test the proposed model, while mediation effects were assessed using standardized indirect effects and the Sobel test. Results show that all eight hypothesized relationships are positive and significant. ESC directly improves export performance while strengthening EMO and EDA, and EMO also positively influences EDA. EDA is the strongest direct predictor of export performance (β = 0.465), whereas both EMO and EDA significantly mediate the relationship between ESC and export performance. The model explains 72.0% of the variance in export performance, highlighting the complementary roles of export communities, market orientation, and digital agility in enhancing SME export competitiveness in an increasingly digitalized global market.